Penerapan Sistem Pengendalian Manajemen Terhadap Perilaku Etis Karyawan Pada PT. Sumber Alfaria Trijaya Cabang Demak - Anastasya Mechta Mediana; Herny Ria Mandag; Hwihanus Hwihanus (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Ethical employee behavior significantly influences company performance, including consumer trust, productivity, and costs. The Management Control System (MCS) is a crucial instrument in achieving organizational goals and shaping the ethical behavior of employees. Individual, organizational, and environmental factors play a key role in forming ethical employee behavior. This study focuses on PT. Sumber Alfaria Trijaya Branch Demak, the largest retail company in Indonesia, which is committed to implementing ethical behavior. Literature review highlights the importance of ethical employee behavior, noting its positive impact on consumer trust, productivity, and corporate reputation. MCS is described as a key element in maintaining ethical behavior, with ethical culture, behavioral standards, and monitoring mechanisms as its components. The research methodology employed is qualitative descriptive research with a literature review approach. The study aims to analyze the influence of implementing MCS on the ethical behavior of employees at PT. Sumber Alfaria Trijaya Branch Demak. Data were obtained from books, articles, journals, and interviews with company employees. Data collection techniques involved literature review and interviews, with qualitative analysis using the inductive method.